2021
DOI: 10.1007/s40615-020-00942-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 Information Overload Among the General Public

Abstract: Background A relentless flood of information accompanied the novel coronavirus 2019 (COVID-19) pandemic. False news, conspiracy theories, and magical cures were shared with the general public at an alarming rate, which may lead to increased anxiety and stress levels and associated debilitating consequences.Objectives To measure the level of COVID-19 information overload (COVIO) and assess the association between COVIO and sociodemographic characteristics among the general public. Methods A cross-sectional onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 25 publications
4
80
0
9
Order By: Relevance
“…During the COVID-19 pandemic, many people experienced information overload (Hong and Kim, 2020;Mohammed et al, 2021), which in health information-related contexts is often defined as the feeling of being overwhelmed by the sheer amount of information (Jensen et al, 2014). Importantly, information overload can also be felt when information about COVID-19 is provided offline via broadcast-in this case, people have little control over what information they take in compared to when they seek information on social media (Mohammed et al, 2021).…”
Section: Dealing With Online Scientific Information About Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, many people experienced information overload (Hong and Kim, 2020;Mohammed et al, 2021), which in health information-related contexts is often defined as the feeling of being overwhelmed by the sheer amount of information (Jensen et al, 2014). Importantly, information overload can also be felt when information about COVID-19 is provided offline via broadcast-in this case, people have little control over what information they take in compared to when they seek information on social media (Mohammed et al, 2021).…”
Section: Dealing With Online Scientific Information About Covid-19mentioning
confidence: 99%
“…During the COVID-19 pandemic, many people experienced information overload (Hong and Kim, 2020;Mohammed et al, 2021), which in health information-related contexts is often defined as the feeling of being overwhelmed by the sheer amount of information (Jensen et al, 2014). Importantly, information overload can also be felt when information about COVID-19 is provided offline via broadcast-in this case, people have little control over what information they take in compared to when they seek information on social media (Mohammed et al, 2021). During the pandemic, people often consumed information from several sources-such as broadcast in addition to social media-and often on a daily basis or even every minute, which can increase feelings of information overload (Hong and Kim, 2020;Motta Zanin et al, 2020;Mohammed et al, 2021).…”
Section: Dealing With Online Scientific Information About Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, COVID-19 information overload (COVIO) has received much attention from researchers around the world (Mohammed et al, 2021;Valika et al, 2020). COVIO is the information overload caused by the pandemic.…”
Section: Sayeed Al-zamanmentioning
confidence: 99%
“…Regarding mediated information consumption, a study revealed that the individuals who receive information from mainstream media than social media are more likely to be affected by COVIO (Mohammed et al, 2021). In contrast, other studies claimed that the consumption of social media has increased remarkably during the pandemic that makes more individuals overloaded with information (Keelery, 2020;Rathore & Farooq, 2020).…”
Section: Sayeed Al-zamanmentioning
confidence: 99%